Involvement of the larynx motor area in singing-voice perception: a TMS study† - Lévêque, Yohana; Muggleton, Neil; Stewart, Lauren; Schön, Daniele (Frontiers in Psychology, 2013)
Recent evidence has reported that the motor system has a role in speech or emotional vocalization discrimination. In the present study we investigated the involvement of the larynx motor representation in singing perception. Twenty-one non-musicians listened to short tones sung by a human voice or played by a machine and performed a categorization task. Thereafter continuous theta-burst transcranial magnetic stimulation was applied over the right larynx pre-motor area or on the vertex and the test administered again. Overall, reaction times were shorter after stimulation over both sites. Nonetheless and most importantly, reaction times became longer for sung than for “machine” sounds after stimulation on the larynx area. This effect suggests that the right premotor region is functionally involved in singing perception and that sound humanness modulates motor resonance.